Assessing the possibilities of designing a unified multistep continuous flow synthesis platform - Sharma, Mrityunjay K.; Acharya, Roopashri B.; Shukla, Chinmay A.; Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2018)
The multistep flow synthesis of complex molecules has gained momentum over the last few years. A wide range of reaction types and conditions have been integrated seamlessly on a single platform including in-line separation as well as monitoring. Beyond merely getting considered as `flow version' of conventional `one-pot synthesis', multistep flow synthesis has become the next generation tool for creating libraries of new molecules. Here we give a more `engineering' look at the possibility of developing a `unified multistep flow synthesis platform'. A detailed analysis of various scenarios is presented considering 4 different classes of drugs already reported in the literature. The possible complexities that an automated and controlled platform needs to handle are also discussed in detail. Three different design approaches are proposed: (i) one molecule at a time, (ii) many molecules at a time and (iii) cybernetic approach. Each approach would lead to the effortless integration of different synthesis stages and also at different synthesis scales. While one may expect such a platform to operate like a `driverless car' or a `robo chemist' or a `transformer', in reality, such an envisaged system would be much more complex than these examples.
Keywords: automation; continuous flow synthesis; cybernetics; multistep flow synthesis; unified platforms

Hydrodynamics and selectivity engineering of a multipoint dosing flow reactor - Shukla, Chinmay A.; Pal, Sayan; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2019)
This paper reports the suitability of a multipoint injection continuous flow reactor for carrying out a sequential reaction, while taking into account the associated hydrodynamics of such systems. Pressure drop was measured for different fluid injection patterns, viz., equal fluid dosing, decreasing dosing, and increasing dosing flow rates from the first to the last inlet. Moreover, residence time distribution was also explored. The data were compared with a conventional single-point injection. The extent of dispersion was found to be higher in the decreasing dosing profile compared to equally distributed dosing. Taking into account of these features, the suitability of such a reactor system for competitive-consecutive homogeneous nitration reaction was evaluated. The analysis was done on the basis of the Damkohler number (Da) for mixing and reaction. The rate-controlling phenomena were used to simulate the performance of the reactor for a range of a number of inlets, the mole ratio of reactants, and relative values of Da. The observations indicate that the multipoint injection is not beneficial for mixing controlled reactions. However, for reactions in the transient regime (i.e., 0.001 < t(m)/t(R) < 1000), it gives higher selectivity of the desired product.

Efficient processing of reactions involving diazonium salts: meerwein arylation in an impinging-jet reactor - Shukla, Chinmay A.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Organic Process Research & Development, 2020)
This work reports a novel approach for performing high-throughput synthesis of Meerwein arylation in an impingingjet reactor. The multistep reaction was performed in a single reactor via in situ diazonium salt generation followed by Meerwein arylation. The work involves many iterations between experiments and simulations (where we integrate simulating the flow, heat transfer, and reaction simultaneously) for optimization of conditions in an inverted impinging-jet reactor. The effect of design variables viz. catalyst concentration, inlet temperature, and monomer mole ratio on the yield of the desired product was studied in detail, and the simulation results were used to plan the continuous experiments. An infrared camera was used to monitor the transient reactor temperature for steady-state analysis. The lab-scale inverted impinging-jet reactor with over 93% isolated yield can offer a space-time yield of 277.78 tons/m(3)/day. The numbering-up of an inverted impinging-jet reactor can be an effective way for cleaner production of products through typical Meerwein arylation.
Keywords: computational fluid dynamics; high throughput synthesis; impinging-jet reactor; IR camera; Meerwein arylation; Numbering-up

Selectivity engineering of Meerwein arylation in a continuous flow reactor: a modelling approach - Shukla, Chinmay A.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2020)
This paper presents a methodology for selectivity engineering of Meerwein arylation in a flow reactor. The reaction was optimized in batch mode and reaction kinetics were obtained over a range of temperatures and catalyst concentrations. A lumped kinetic model was formulated and the parameters were estimated using nonlinear regression. Furthermore, telescopic flow synthesis for Meerwein arylation via in situ diazonium salt generation and coupling was demonstrated. A non-isothermal model was developed and experimentally validated. The effect of initial concentration and inlet temperature on the yield of the desired product was estimated for various catalyst concentrations. The results from the simulations in terms of nondimensional numbers were used to find suitable operating conditions for Meerwein arylation.

Towards sustainable continuous production of azo dyes: possibilities and techno-economic analysis - Shukla, Chinmay A.; Kute, Mahesh S.; Kulkarni, Amol A. (Green Chemistry, 2021)
A novel continuous process for synthesizing azo dyes using a bubble column reactor is reported. Continuous experiments were successfully performed for Sudan-I dye and Solvent Yellow 16 dye with a yield [and productivity] of 92.04 +/- 3.50% [1.68 +/- 0.13 kg day(-1)] and 96.60 +/- 2.18% [1.92 +/- 0.04 kg day(-1)], respectively. Experiments were performed at a higher slurry concentration similar to 5% (w/w) without any clogging. The results were extended for performing a detailed techno-economic analysis for 5 TPD Sudan-I azo dye production as a case study. The results indicate that the cost of the continuous process is almost 4.68 times lower than that of the corresponding batch process. Furthermore, the footprint for a continuous plant can be lowered by 2.4 to 4.5 times when compared to the batch process depending on different refilling strategies for feed storage tanks. A continuous process may require 39-42% less water than the industrial batch process.